Alkylation converts riboflavin into an efficient photosensitizer of phospholipid membranes - Sosa, María José (2023)
A new decyl chain [−(CH2)9CH3] riboflavin conjugate has been synthesized and investigated. A nucleophilic substitution (SN2) reaction was used for coupling the alkyl chain to riboflavin (Rf), a model natural photosensitizer. As expected, the alkylated compound (decyl-Rf) is significantly more lipophilic than its precursor and efficiently intercalates within phospholipid bilayers, increasing its fluorescence quantum yield. The oxidative damage to lipid membranes photoinduced by decyl-Rf was investigated in large and giant unilamellar vesicles (LUVs and GUVs, respectively) composed of different phospholipids. Using a fluorogenic probe, fast radical formation and singlet oxygen generation was demonstrated upon UVA irradiation in vesicles containing decyl-Rf. Photosensitized formation of conjugated dienes and hydroperoxides, and membrane leakage in LUVs rich in poly-unsaturated fatty acids were also investigated. The overall assessment of the results shows that decyl-Rf is a significantly more efficient photosensitizer of lipids than its unsubstituted precursor and that the association to lipid membranes is key to trigger phospholipid oxidation. Alkylation of hydrophilic photosensitizers as a simple and general synthetic tool to obtain efficient photosensitizers of biomembranes, with potential applications, is discussed.